Peningkatan Kapasitas Wirausaha Mahasiswa Melalui Implementasi Program Wirausaha Merdeka - Eris Narulita Putri; Maulidyah Indira Hasmarini (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
The high rate of educated unemployment in Indonesia, especially among college graduates, is a challenge that requires real and sustainable solutions. One of the main factors is the gap between the number of graduates and the availability of relevant jobs. The Wirausaha Merdeka program is one solution to boost entrepreneurship among students. The implementation method employs a hands-on learning approach (learning by doing) comprising two main stages: the pre-immersion stage and the immersion stage (internship). The pre-immersion stage involves providing entrepreneurship-related materials. The immersion stage is conducted in collaboration with internship partners, where students gain practical experience in managing a business, followed by acceleration for business development, proposal pitching presentations, and an entrepreneurship expo. The results of the program indicate that students not only acquire knowledge and practical skills in entrepreneurship but also enhance their self-confidence, creativity, and build a beneficial business network for future business development. Thus, the Wirausaha Merdeka Program has a positive impact in reducing the rate of educated unemployment through the empowerment of students' entrepreneurial potential.